Merocyanine Dyes with Extended Polymethine Chains by Simple Two-Step Condensation Sequence - Arjona-Esteban, Alhama; Rausch, Anja; Vysotsky, Myroslav O.; Würthner, Frank (Synthesis, 2021)
We describe a synthetic method for the synthesis of merocyanine dyes containing a bridge with three conjugated double bonds. This method consists of two successive condensation reactions. The first one is made between CH-acidic indane-1,3-dione acceptor units and an appropriate ketone (here acetone or hexan-2-one). The extended acceptor thus obtained is condensed with an aldehyde in the next step. The dyes show high tinctorial strength due to intense absorption bands at wavelengths between 500 and 750 nm.
Keywords: Knoevenagel condensation; merocyanine dyes; UV-vis absorption spectroscopy; polymethine chain elongation